Chaotic Image Encryption System as a Proactive Scheme for Image Transmission in FSO High-Altitude Platform - Ping Zhang; Jingfeng Jie; Zhi Liu; Keyan Dong (Photonics)
To further enhance the stability and security of image transmission in FSO (Free Space Optics) aviation platforms, this paper proposes a communication transmission scheme that integrates a chaotic image encryption system with the HAP (high-altitude platform) environment. This scheme effectively combines the chaotic image encryption algorithm with the atmospheric turbulence channel transmission process, improving the anti-interference capabilities and security of HAP optical communication for image transmission. First, a five-dimensional hyperchaotic system with complex dynamic characteristics is introduced, and the system’s chaotic behaviors and dynamic properties are explored. The improved system model incorporates chaotic mapping and DNA coding techniques, forming a robust chaotic image encryption system, whose performance is experimentally validated. Next, the feasibility of integrating the chaotic image encryption system with HAP optical communication is discussed. A detailed description of the corresponding turbulence model and test conditions is provided. To verify the scheme’s feasibility, plaintext images of varying sizes are selected for experiments, comparing the transmission performance of both unencrypted and encrypted images under three turbulence levels: weak, medium, and strong. The impact on image communication quality is quantitatively analyzed using PSNR (Peak Signal-to-Noise Ratio) and SSIM (Structural Similarity Index measure). Finally, the effect of malicious interception attacks, caused by noise interference from different levels of atmospheric turbulence, is examined. The robustness and feasibility of the proposed scheme are validated, providing a promising approach for integrating HAP optical communication’s anti-turbulence capabilities with chaotic image encryption.